1997
DOI: 10.1523/jneurosci.17-16-06434.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Hippocampus, the Bed Nucleus of the Stria Terminalis, and the Amygdala in the Excitatory Effect of Corticotropin-Releasing Hormone on the Acoustic Startle Reflex

Abstract: Previously, we demonstrated that transection of the fimbria/ fornix blocked the excitatory effect of corticotropin-releasing hormone (CRH) on startle (CRH-enhanced startle), suggesting that the hippocampus and its efferent target areas that communicate via the fimbria may be critically involved in CRHenhanced startle. The bed nucleus of the stria terminalis (BNST) receives direct projections from the ventral hippocampus via the fimbria/fornix. Therefore, the role of the ventral hippocampus, the BNST, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
307
3
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(344 citation statements)
references
References 66 publications
33
307
3
1
Order By: Relevance
“…Chemical lesions of the BNST, but not lesions of the amygdala or of the ventral hippocampus, prevent CRH-enhanced startle (Lee and Davis 1997). Infusion of CRH in the BNST, but not in the amygdala mimics the ICV CRH effect (Liang et al 1992) and infusion of the CRH-receptor antagonist alpha-helical CRH in the BNST blocks CRH-enhanced startle (Lee and Davis 1997). These results implicate the BNST rather than amygdala as the primary source for the anxiogenic effect of CRH on startle, pointing to a selective role of CRH in the BNST as a potential mechanism for anxiety states.…”
Section: Preclinical Evidence For Dissociated Neural Systems Of Fear mentioning
confidence: 93%
“…Chemical lesions of the BNST, but not lesions of the amygdala or of the ventral hippocampus, prevent CRH-enhanced startle (Lee and Davis 1997). Infusion of CRH in the BNST, but not in the amygdala mimics the ICV CRH effect (Liang et al 1992) and infusion of the CRH-receptor antagonist alpha-helical CRH in the BNST blocks CRH-enhanced startle (Lee and Davis 1997). These results implicate the BNST rather than amygdala as the primary source for the anxiogenic effect of CRH on startle, pointing to a selective role of CRH in the BNST as a potential mechanism for anxiety states.…”
Section: Preclinical Evidence For Dissociated Neural Systems Of Fear mentioning
confidence: 93%
“…The role of the extended amygdala in fear and anxiety is well established (Davis 1992, Davis et al 1994, Lee & Davis 1997, Merali et al 2003, Schulkin et al 1998. It has been shown that infusion of CRH into the BNST and amygdala provokes number of fear-related behavioral responses in a CRH1R receptor dependent manner (Lee & Davis 1997, Shepard et al 2000.…”
Section: The Integrated Stress Response-view From Crhmentioning
confidence: 99%
“…It has been shown that infusion of CRH into the BNST and amygdala provokes number of fear-related behavioral responses in a CRH1R receptor dependent manner (Lee & Davis 1997, Shepard et al 2000.…”
Section: The Integrated Stress Response-view From Crhmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that HPA-axis becomes activated during stimulation of rat amygdala, along with an increase in the level of corticosterone in serum and symptoms that are similar to those observed during stress response, such as freezing [30] . CRH administration in a chemical lesion of the amygdala failed to induce the behavioral effects [31] . Furthermore, application of a CRH antagonist in the amygdala could significantly reduce the response to repeated stress [33] .…”
mentioning
confidence: 97%